Percanggahan Waktu Mustajab Doa Hari Jumaat: Analisis Kaedah Tarjīḥ Al-suyūṭῑ Menurut Perspektif Hadis Mawḍu‘ī - Mohd Nor Adzhar Ibrahim; Muhammad Akmalludin Mohd Hamdan; Roshimah Shamsudin; Mohd Solleh Ab Razak; Wan Khairul Aiman Wan Mokhtar (USIM Press, 2025)
Indexed by MyCite